Patient medication counselling in community pharmacy: evaluation of the quality and content (2022)
Background: Patient medication counseling (PMC) is a pharmaceutical care service targeted at optimizing patient drug use, safety and improving treatment outcomes. This study assessed the content and quality of PMC from the community pharmacists’ (CPs) and pharmacy customers’ (PCs) perspectives. Methods: A cross-sectional questionnaire-guided survey was conducted in Ibadan, Nigeria, among 125 CPs and 612 PCs. The 35-counselling items validated United States Pharmacopeia Medication Counseling Behavior Guideline scale with 10-point graded responses (1 = poor to 10 = excellent) was used. Self-reported medication counseling information content provided by CPs and received by PCs was assessed and expressed in median and interquartile ranges. The quality of PMC was evaluated and graded as poor (1–29.9%), unsatisfactory (30–59.9%), satisfactory (60–79.9%) and excellent (80–100%). Associations between demographic variables and overall quality of counseling were determined with Mann–Whitney U and Kruskal–Wallis tests at p < 0.05. Results: The response rate was 92.5% and 97.6% for PCs and CPs, respectively. The PCs’ opinions on the individual content of the PMC provided by the CPs were significantly different from the pharmacists’ self-report (p < 0.05). Some of the PMC content included how to take the medicine PC = 6.00 (2.00) vs CP = 8.00 (2.00), information on possible side effects PC = 6.00 (2.00) vs CP = 8.00 (2.00), taking history of allergies and other medications PC = 6.00 (6.00) vs CP = 7.00 (1.00), and how to incorporate drug regimen into daily routine PC = 5.00 (6.00) vs CP = 8.00 (3.00). The quality of PMC purportedly provided by CPs and received by the PCs was satisfactory (75%) and unsatisfactory (55%), respectively. The quality of communication counseling offered by CPs trained in Nigeria (Mean rank = 62.49) was higher than those trained outside Nigeria (Mean rank = 26.40), U = 228.00, p = 0.024. The PC’s age, marital status, and highest educational qualification were significantly associated with their opinion on the quality of counseling received. Conclusions: Both the community pharmacists and pharmacy customers reported the provision of patient medication counseling on side effects, drug usage, medication history and allergies among others. However, the quality of counseling provided by the pharmacists was satisfactory, but the quality of counseling received by the pharmacy customers was unsatisfactory. Pharmacists may need to engage pharmacy customers more during medication counseling